Increase of peripheral blood TCD8+ cells in women with recurrent miscarriage. (January 2014) - Ghafourian, M.; Abuhamidy, A.; Karami, N.
<x xml:space="preserve">Abstract</x> Recurrent miscarriage (RM) is one of the most prevalent reproductive problems faced by couples that may affect as many as 2% of women in reproductive age. The causes of its abnormality have attracted the attention of many researchers. We aim to determine the different T-cell subsets in women with RM and normal control. In this prospective case–control study, peripheral blood was taken from women with RM (n = 25) and normal women (n = 17), during the mid-luteal phase. The percentage of CD3, CD3+CD4+, CD3+CD8+ markers and also CD4/CD8 ratio was detected in the patients and control group by flow cytometry. The proportion of TCD8+ was significantly higher in RM women compared with the control group (p < 0.05). However, there was no statistical difference in percentage of total TCD3+ and TCD4+ cells between the RM and control women. Also, the CD4/CD8 ratio was lower in the RM women compared with the control women. These observations support the concept that increase of TCD8+ lymphocytes could be involved in the aetiology of RM.